Employment Law Perspective and Mutual Respects in Resolving Industrial Relation Issue; The Case of Labor Strike in Demanding Wage Increase of PT Freeport Indonesia Employees - Rumainum, Jonathan; Saksono, Prasetyo B. (The Indonesian Journal of Business Administration, 2012)
Few factors has been identified as the cause of the interruption in Industrial relationship in PTFI which bring consequence in the suspend of negotiation thus followed by extended labor strike. The factors are the basic reference in increase wage demand, dead lock decision in -CLA negotiationÂ as cause of labor strike, the Industrial relationship settlement approach after the -CLAÂ negotiation stopped. The main cause of the problem is the discrepancy in understanding and communication as the consequence of each party keep hold tight on its principle and interest. Beside the material loss, the company also suffers physiological effect after the labor strike as the consequence of intimidation to non strike workers. To rebuild harmonious Industrial relationship in PTFI, the company and its employee needs to understand about industrial relationship principals with always consider the mutual interest, partnership, and interdependence, create calm and peacefully working atmosphere, increase productivity and increase mutual welfare. Start everything with good intention and industrial relationship approach together with mutual trust , if there is dispute in relationship. One of the Industrial relations- tool that needs to be develop in PTFI is communication in partnership relations- with equivalent position between company and labor union through -the bipartite coorporation body ( LKS- Bipartit). Key Words: Regulation No.13 Year 2003, Industrial Relationship, Mutual Agreement, Wages, Labor Strike, Industrial relationship dispute, Mutual respect / trust..Â